P12.06 Genital trichomonas vaginalis is rare among female attendees at a sydney metropolitan sexual health clinic. (13th September 2015) - Tilley, DM; Dubedat, SM; Lowe, P; Templeton, DJ
Abstract : Introduction: Trichomonas vaginalis (TV) is the most common non-viral sexually transmitted infection worldwide. Among Australian women, a wide variation in prevalence (0.38%–8.4%) using nucleic acid amplification tests (NAAT) has been reported. Our aim was to assess whether routine screening for TV in females is indicated in an urban Australian setting. Methods: Females attending a sexual health clinic from July 2013–February 2014 who were tested for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) were eligible to have a TV test on the same specimen. Testing was performed by transcription-mediated amplification on female genital specimens using the Aptima Trichomonas vaginalis assay (Hologic Inc., United States). Characteristics of the study population were examined. Results: During the study period, 393 women were tested for CT/NG on 471 occasions. TV tests were performed 347 (73.7%) of CT/NG specimens. There were no significant differences between women who had (n = 294), and did not have (n = 99), a TV test during the study period, except that women who had recent overseas sexual contact were less likely to be tested. Of the 347 tests, two TV infections were diagnosed, a positivity rate of 0.6% (95% CI 0.07–2.1%). Both cases were Australian-born with a history of injecting drug use in the past 12 months, Neither were sex workers and one identified as Aboriginal. One presented with post-coital bleeding, and TV was identified on wet film. The other reported pelvic symptoms, but was tested on outreach and no wet film microscopy was performed. Neither had concurrent CT/NG infections detected. Conclusion: We found a low positivity rate of TV among female attendees. Both TV infections were in women who had symptoms suggestive of a sexually transmitted infection. Our findings are in accord with those from previous urban Australian studies and do not support routine TV screening for asymptomatic women in metropolitan Sydney. Disclosure of interest statement: Aptima Trichomonas vaginalis assay testing kits were provided free by Hologic (Australia) Pty Ltd.